Uma abordagem filosófica sobre a reificação em História e Consciência de Classe de Georg Lukács - Mendes, Bruno Moretti Falcão (2012)
The main purpose of this dissertation is to analyze the philosophical discussion around Reification developed by Georg Lukács in History and Class Consciousness (1923). In this piece, the discussion of Reification presents its originality, so, for Marx the discussion of Reification was centered mainly on the material relations among men within the productive process, in History and Class Consciousness however the theory is connected to the process of material formation of the reified objectivity. This theory would be built within the development of German classical philosophy, since as Lukács first analyzes the objective forms of Reification within the socioeconomic structure the conceptualization of Reification based on Marx economic analysis and this takes to the displacement of the problem of the reified formation of consciousness in the philosophical thinking, Lukács presents his materialist interpretation of the consciousness formation: this last one possesses a material formation basis, determined by the capitalist production of commodities. This displacement represents a connection between Marxism and German classical philosophy around the issue of forming the Subject in History. In this dissertation our efforts are directed to understand the way, according to Lukács, German classical philosophy strives to produce in the History a self-knowing universal Subject and as this striving reaches the fetishist limit of its own reified formation. The main purpose is to reveal how, according to Lukács, the consciousness formation corresponds to the fetish; formation analyzed in the historical progression of bourgeois antinomic thinking. This progression corresponds to the several levels of problematisation of the Being and to the attempts of the reified subjectivity s overcoming within the development of German classical philosophy. Our perspective seeks the understanding of how the progression of antinomies allows the dialectical interpretation of the material foundations that determine the formation of consciousness in the philosophical level.